2015
DOI: 10.1126/scisignal.aac7135
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of H 2 S during obesity enhances store-operated Ca 2+ entry in adipose tissue macrophages to increase cytokine production

Abstract: The increased production of proinflammatory cytokines by adipose tissue macrophages (ATMs) contributes to chronic, low-level inflammation during obesity. We found that obesity in mice reduced the bioavailability of the gaseous signaling molecule hydrogen sulfide (H2S). Steady-state, intracellular concentrations of H2S were lower in ATMs isolated from mice with diet-induced obesity than in ATMs from lean mice. In addition, the intracellular concentration of H2S in the macrophage cell line RAW264.7 was reduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 68 publications
0
24
1
Order By: Relevance
“…However, prolonged inflammatory reactions may not only retard the wound‐healing process but also favor tissue fibrosis, which reduces the possibility of true regeneration (Arancibia et al., ). Another study showed that the bioavailability of H 2 S was reduced in obese mice with increased pro‐inflammatory cytokine levels, and the increased pro‐inflammatory cytokine production was prevented by the exogenous H 2 S donor GYY4137 (Velmurugan et al., ). These results collectively suggest that the inflammatory microenvironment can inhibit the production of endogenous H 2 S, and in the normal wound‐healing processes, the supplemental H 2 S might delay the wound‐healing quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged inflammatory reactions may not only retard the wound‐healing process but also favor tissue fibrosis, which reduces the possibility of true regeneration (Arancibia et al., ). Another study showed that the bioavailability of H 2 S was reduced in obese mice with increased pro‐inflammatory cytokine levels, and the increased pro‐inflammatory cytokine production was prevented by the exogenous H 2 S donor GYY4137 (Velmurugan et al., ). These results collectively suggest that the inflammatory microenvironment can inhibit the production of endogenous H 2 S, and in the normal wound‐healing processes, the supplemental H 2 S might delay the wound‐healing quality.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in M 1 markers such as IL-6, IL-1β, and inducible nitric oxide synthase and decrease in M 2 markers such as arginase-2 or mannose receptor C type 1 (MRC1) in obese mice are reversed by GYY4137 as well as SOCE inhibitors. Overall, these results indicate that H 2 S deficiency contributes to SOCE activation and proinflammatory phenotype switch of adipose tissue macrophages associated with obesity [ 77 ].…”
Section: Hydrogen Sulfide and Dysregulation Of Adipokine Productiomentioning
confidence: 98%
“…It has been reported that the increased H 2 S circulation detected in the burn injury [36] and its levels correlated with inflammatory and clinical indices in rheumatoid arthritis patients [37]. Moreover, multiple lines of studies, in multiple experimental models, showing that therapeutic elevation of H 2 S concentrations or H 2 S donors can exert anti-inflammation and decrease the mortality caused by endotoxemia [38][39][40]. We found that CSE expression was significantly increased in LPS-induced macrophage, which were accompanied by increased inflammatory mediators and inflammatory cytokines production.…”
Section: Figmentioning
confidence: 99%